The Third Chimurenga:The discursive construction of exclusion through the land reform in Zimbabwe: Paper presented at the Faculty of Arts Land Reform Conference, 29-30 September 2017 at Midlands State University, Zvishavane Campus – Zimbabwe - Mangeya, Hugh (Midlands State University, 2018)
Zimbabwe’s land reform marked a defining period in Zimbabwe’s history as a nation. Different scholars have alternatively referred to this period from the perspectives of crisis, nationalism or redress of historical [land] imbalances. The present research looks at the ways in which the state narratives about the land used language/discourse to reconfigure, among other things, national identities. It was a period whereby the hitherto liberation struggle mwana wevhu (‘son of the soil’) discourse was invoked and deployed in the discourse of ‘Othering’ which mainly separated the ‘Us’ (ZANU-PF) from the ‘Them’ (MDC/opposition). It was a period in which, by extension, the label of vatengesi (‘sell outs’) also became highlighted, thereby constituting defining ZANU PF slogans and graffiti that also became important discursive tools for discrimination. The study adopted a quasi-corpus linguistic approach in which songs, political jingles and slogans, the state and private media (The Herald and Daily News, respectively) were analysed. The study is couched in a conceptual framework that is mainly informed by the Critical Discourse Analysis and Cognitive Linguistics theoretical frameworks.